Practices influencing weight reduction among adults participating at Gym centers in Jaffna District - Mathangan, S; Aarabi, M; Kamalarupan, L; Sabaananth, S (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Weight loss is a decrease in body weight achieved either through diet and exercise or due to involuntary circumstances such as illness. Previous studies in different settings have shown that dietary changes, such as ketogenic and vegetarian diets, together with physical activity, are widely used strategies for weight management. In South Asian contexts, traditional practices such as Ayurvedic medicine have also been linked to weight reduction. However, limited information is available on the specific practices followed by gym participants in the Jaffna district. Objective: To assess the practices for weight reduction by adults who participated in the gym centers in the Jaffna district. Methodology: A descriptive cross-sectional study was conducted among gym participants in the Jaffna district aged between 18 and 60 years. A total of 298 participants were selected, and the required number of samples from each gym was calculated on the basis of population proportion. The required number of participants was recruited for the study by using convenience sampling methods, as it allowed easy access to gym participants within the study area during the data collection period. Data were collected through a validated, interview-administered questionnaire consisting of four sections. Analysis was performed using SPSS version 27. Ethical clearance was obtained from the Ethical Review Committee, Faculty of Medicine, University of Jaffna. Results: A total of 298 participants (age 18–60 years) were included, with a 100% response rate. The ketogenic diet (56.0%) and the vegetarian diet (53.4%) were the most common dietary practices. Flexibility and balanced exercises (69.1%) and cardiovascular/aerobic exercises (50.0%) were the most frequently performed. Evidence from Korea suggests that these exercise types are linked to lower cardiovascular mortality. Most participants reported not using any medications for weight reduction, while 11.7% indicated the use of Ayurvedic medicines. Conclusion: The study shows that a lot of participants choose healthy practices to overcome weight reduction, like choosing a ketogenic diet, flexibility and balanced exercise, and Ayurvedic medication for weight reduction. These practices not only support effective weight management but also suggest the importance of integrating cultural perspectives into weight loss interventions. The findings provide baseline evidence to guide future health promotion programs in the region.
Keywords: Ayurvedic medication; Weight reduction practices; Gym participants; Exercise; Dietary pattern